Microneedle Delivery of Heterologous Microparticulate COVID-19 Vaccine Induces Cross Strain Specific Antibody Levels in Mice - Tanisha Manoj Arte; Smital Rajan Patil; Emmanuel Adediran; Revanth Singh; Priyal Bagwe; Mahek Anil Gulani; Dedeepya Pasupuleti; Amarae Ferguson; Susu M. Zughaier; Martin J. D’Souza (Vaccines)
Background: In recent years, the COVID-19 pandemic has significantly impacted global health, largely driven by the emergence of various genetic mutations within the SARS-CoV-2 virus. Although the pandemic phase has passed, the full extent of the virus’s evolutionary trajectory remains uncertain, highlighting the need for continued research in vaccine development to establish a cross-reactive approach that can effectively address different variants. This proof-of-concept study aimed to assess the effectiveness of microparticulate vaccine delivery through the minimally invasive microneedle route of administration, using a heterologous prime–booster strategy against the SARS-CoV-2 virus. Method: This strategy uses the whole inactivated virus of the Delta variant for the prime dose and the whole inactivated virus of the Omicron variant for the booster dose, with alum as an adjuvant. The formulation of microparticles involves encapsulating the antigens in poly lactic-co-glycolic acid (PLGA) polymer, which provides sustained release and enhances immunogenicity while protecting the antigen. Microparticles were tested for in vitro assays, and characterization included particle size, zeta potential, and encapsulation efficacy. Furthermore, serum was collected post-administration of the vaccine in mice and was tested for antibody levels. Result: In vitro assays confirmed the non-cytotoxicity and the ability of microparticles to activate the immune response of the vaccine particles. Administering this microparticulate vaccine via microneedles has proven effective for delivering vaccines through the skin. We also observed significantly higher antigen-specific antibody levels and cross-reactivity in the strains. Conclusions: Our adjuvanted microparticulate-based heterologous prime–booster vaccine strategy showed cross-reactivity among the strains and was successfully delivered using microneedles.